2014
DOI: 10.1007/s10508-014-0360-9
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS-related Knowledge and Behaviors Among Rural Married Migrant Women in Shandong Province, China: A Comparison Study

Abstract: Migrant women in China are disproportionately affected by HIV/AIDS. This study described HIV/AIDS-related knowledge and behaviors among married migrant women in Shandong province in comparison to non-migrant local women and identified factors associated with HIV testing history and extramarital sex among married migrant women. A probability-based sample of 1,076 migrant and 1,195 local women were included in the analyses. Compared to local women, married migrant women had lower levels of HIV/AIDS knowledge and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…[ 25 ] Previous studies have reported that lack of HIV/AIDS-related prevention knowledge is associated with greater likelihood of premarital sex, extramarital sex, history of sexually transmitted diseases, and drug use. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Previous studies have reported that lack of HIV/AIDS-related prevention knowledge is associated with greater likelihood of premarital sex, extramarital sex, history of sexually transmitted diseases, and drug use. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has further indicated that migrants, compared to local residents, have less access to HIV testing. For example, a recent study, conducted in migrant women and local women, suggested that HIV testing was less common in migrant women than in local women ( Song et al , 2015 ). Our results were similar with this study by indicating migrant MSM also have less access to HIV/STIs testing compared with local MSM.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that married migrant women were more likely to have HIV-related behaviors (i.e., blood transfusion, premarital sex, extramarital sex, sexually transmitted diseases and drug use), and less likely to have an HIV test [35]. We find that higher total social support score is related to better awareness of AIDS/ STD infection.…”
Section: Discussionmentioning
confidence: 45%